Role of housing reconstruction between years 2000-2014 in merging of urban structure of the North-East Wrocław = ola zabudowy mieszkaniowej z lat 2000-2014 w scalaniu struktury urbanistycznej północno-wschodniego Wrocławia - Masztalski, Robert; Michalski, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the urban structure of the North-East of Wroclaw, where in the vicinity of the historic buildings and residential buildings from the 70s of the last century, and between, in the last 20 years there were built new buildings, as binding material of the urban structure. The new multifamily housing development of years 2000-2014 of Psie Pole as a housing development in Wroclaw, closes the gap between the historic district residential buildings in the old Psie Pole and the buildings of large slabs of the 70s of the twentieth century.
Keywords: urbanistyka; osiedle mieszkaniowe; infrastruktura społeczno-usługowa; przestrzeń zurbanizowana; city planning; housing development; services and social infrastructure; urban space transformations